2011
DOI: 10.5539/jsd.v4n6p3
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Influence of Service Recovery Satisfaction on Destination Loyalty: A Structural Equation Modelling

Abstract: Total tourists' holiday experiences to a certain extent are affected by their experiences staying at a hotel. Although service providers strive for "doing it right" the first time, but service failures are inevitable in the hospitality industry. Most service providers usually undertake to recover the service failure, through efforts such as giving explanation, compensations and apology, when service failures occur. The main aim of this research is to explore the drivers of service recovery satisfaction among f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Applying SEM method, this study contributes to the academic knowledge by examining tourism theory in the context of Vietnam. This study also improves previous research model in tourism marketing (Yüksel and Akgül, 2007, Chen and Tsai 2007, Žabka et al, 2010, and Mohamad et al, 2011 by adding the important factors of promotional activities and tourist expectation. Our model gives a more extended and integrated vision of the effects of promotional activity and tourist expectation on tourist satisfaction and destination loyalty was proposed and tested in all phases of tourist decision-making.…”
Section: Academic Contributionsmentioning
confidence: 80%
See 2 more Smart Citations
“…Applying SEM method, this study contributes to the academic knowledge by examining tourism theory in the context of Vietnam. This study also improves previous research model in tourism marketing (Yüksel and Akgül, 2007, Chen and Tsai 2007, Žabka et al, 2010, and Mohamad et al, 2011 by adding the important factors of promotional activities and tourist expectation. Our model gives a more extended and integrated vision of the effects of promotional activity and tourist expectation on tourist satisfaction and destination loyalty was proposed and tested in all phases of tourist decision-making.…”
Section: Academic Contributionsmentioning
confidence: 80%
“…Žabka et al (2010) indicate that the perceived quality of a destination's offerings as a formative construct does not permit the generalization of the relevant indicators across different destinations. Therefore, the relationship of promotional activity, tourist expectation, tourist satisfaction and destination loyalty in this study may provide a more specific approach to the core of the study, and the concept and degree of customer loyalty as two critical indicators can measure the success of a product-marketing strategy applied in the tourism industry (Mohamad et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chi and Qu [6] conclude that attribute satisfaction is antecedent to overall satisfaction and that attribute satisfaction and overall satisfaction are both determinants of loyalty. In addition, Mohamad et al [25] provide empirical evidence that confirmed the positive and significant relationship between tourist satisfaction and destination loyalty. From the findings of previous literature reviews, this study proposes the following hypotheses:…”
Section: Literature Reviewmentioning
confidence: 92%
“…Thus, service recovery efforts can only be effective if higher education institutions can ensure that fair interaction and outcome are provided. A fair interaction is one that includes an apology that is sincere and an explanation of what had prompted the service failure to occur and an undertaking to address the service failure (Mohamad, Abdullah & Mokhlis, 2011). Assefa (2014) avers that interaction plays a critical role during service failure and recovery.…”
Section: Interactional Justicementioning
confidence: 99%